Improved Understanding of Student Concepts and Skills in Volleyball Learning through Mobile Learning - Widha Sismahendra; Agus Rusdiana; Yunyun Yudiana (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
The development of information systems that is increasingly influential in various aspects of life, one of which is the world of education. One result of the development of information technology that can be utilized in education is mobile learning (M-Learning). The use of M-Learning in volleyball learning at the elementary school level is still rarely developed and used. Though this media can be a means of supporting education can make the learning process active, creative and innovative. M-Learning can enhance learning activities so that it can foster enthusiasm and student motivation. This can help improve students' understanding and volleyball skills which include volleyball, service, passing, and set-up techniques. The research method used is a quasi-experimental method with a nonequivalent control group design. The results showed that M-Learning can improve student understanding and student skills in volleyball learning. M-Learning can improve learning communication between students, both with friends and teachers so that learning creates active and conducive relationships. This has an impact on increasing student motivation. This improvement can improve students' understanding and skills in volleyball learning.